Literature Review on the Effectiveness of E-Presence in Enhancing Teacher Discipline - Hanama, Akhmad; Hidayati, Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the role of e-presence in improving teacher discipline through a literature review. The research uses qualitative methods, including formulating research problems, collecting relevant literature, reviewing the materials, and analyzing the data. The primary data sources are national journal articles published from 2012 to 2022, with six articles deemed relevant to the topic. The findings indicate that e-presence effectively enhances teacher discipline by facilitating accountability, accurately tracking attendance, and promoting punctuality. Additionally, the use of e-presence systems is associated with better time management and adherence to institutional policies. This research highlights the importance of adopting technological solutions, such as e-presence, in educational institutions to address disciplinary issues among teachers. By ensuring transparent monitoring and fostering professionalism, e-presence serves as a valuable tool to improve teacher performance and institutional efficiency. These findings provide significant insights for policymakers and educational leaders in implementing innovative strategies to optimize teacher discipline.